Clinicopathological characteristics and treatment outcomes of luminal B1 breast cancer in Taiwan. Issue 2 (7th February 2022) - Chen, Bo-Fang; Tsai, Yi-Fang; Huang, Chi-Cheng; Hsu, Chih-Yi; Lien, Pei-Ju; Wang, Yu-Ling; Lin, Yen-Shu; Feng, Chin-Jung; King, Kuang-Liang; Chiu, Jen-Hwey; Chau, Gar-Yang; Tseng, Ling-Ming
Abstract : Background: Hormone receptor-positive, human epidermal growth factor receptor II (HER2)-negative luminal B1 breast cancer is associated with a higher risk of disease relapse than luminal A breast cancer. Therefore, we assessed and compared the distant metastasis pattern and clinical outcomes associated with luminal B1 and luminal A breast cancer in an Asian population. Methods: In this observational study, we assessed patients with estrogen receptor-positive, HER2-negative breast cancer who underwent surgery from 2009 to 2016. Patients were classified into luminal A or luminal B1 subsets via immunohistochemical analysis. Disease-free survival, post-metastasis survival, and overall survival were estimated; time to disease relapse and patterns of distant metastasis were compared. Risk of relapse and mortality were assessed using Cox proportional hazards model. Results: Patients with luminal B1 breast cancer (n = 677) were significantly younger and had larger tumors and a higher degree of affected axillary lymph nodes, lymphovascular invasion, and tumor necrosis than those with luminal A breast cancer (n = 630). Higher rates of local recurrence and distant metastasis were observed for luminal B1 (both p < 0.05); however, no difference was observed in the specific distant metastatic sites. We observed a significant increase in disease relapse risk in luminal B1 patients compared with that in luminal A (hazard ratio: 2.157, 95% CI: 1.340-3.473, p < 0.05). Patient age, tumor size, stage, lymphovascular invasion, and receiving chemotherapy and hormone therapy were independent risk factors for metastasis and recurrence. Only the luminal B1 subtype (hazard ratio: 5.653, 95% CI: 1.166-27.409, p < 0.05) and stage (hazard ratio: 3.400, 95% CI: 1.512-7.649, p < 0.05) were identified as independent risk factors for post metastatic mortality. Conclusion: Luminal B1 breast cancer has aggressive tumor biology compared with luminal A breast cancer in the follow-up period. However, there was no significant difference in the disease relapse pattern between the groups.